2012
DOI: 10.1111/j.1440-0960.2012.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of positive patch test reactions to preservatives: The Australian experience

Abstract: Formaldehyde was the most prevalent preservative allergen. Chloroacetamide allergy was more commonly seen in Australia. Parabens, 2-bromo-2-nitropropane-1,3-diol and benzyl alcohol were the least frequent sensitisers. Household products in Australia are not required to list all ingredients preventing sensitised individuals from properly assessing their exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Effects on the tissue for up to 14 days are recorded (OECD, 2001). Human studies using 5% benzyl alcohol induced positive dermal responses in 0-0.92% of subjects (Chow, Avolio, Lee, & Nixon, 2013;Nair, 2001).…”
Section: Resultsmentioning
confidence: 97%
“…Effects on the tissue for up to 14 days are recorded (OECD, 2001). Human studies using 5% benzyl alcohol induced positive dermal responses in 0-0.92% of subjects (Chow, Avolio, Lee, & Nixon, 2013;Nair, 2001).…”
Section: Resultsmentioning
confidence: 97%
“…In the Danish study, 5 of 302 patients were found to be sensitized ; in a UK study, 2 of 517 patients were found to be sensitized ; and in France, a case of sensitization attributable to a preserved oxidation product was found . Also when consecutive patients were patch tested with chloroacetamide, similar prevalences of contact allergy were noted, for example as many as 2.1% positive reactions, one‐third of which were considered to be relevant (past or present; not stated), in 4451 Australian patients , or 0.8% positive reactions in 80 824 patients tested with a special series, ‘ topical antiseptics’, in the IVDK . According to a market survey of cosmetics conducted in 2006–2009 in Germany, chloroacetamide was hardly used in cosmetics at the time (0.1% of 4680 products) .…”
Section: Antimicrobial Substances and Preservativesmentioning
confidence: 91%
“…MCI/MI is an extreme sensitizer. When it was tested in baseline patch test series, the contact allergy rates in dermatitis patients varied between 2.1% and 4.1% (17,(19)(20)(21)(22). In a European multicentre study, the contact allergy rate was fairly stable, at between 2% and 2.5%, over a period of 10 years (23).…”
Section: Sensitizing Potencymentioning
confidence: 99%